Animal diversity and ecosystem functioning in dynamic food webs - Florian D. Schneider (Nature Portfolio, 2016)
Losing animals from food webs could reduce ecosystem function, but drivers of this pattern are difficult to disentangle. With food web simulations, Schneider et al. show that high animal diversity does not release plants from top-down control owing to a balancing effect of increased animal body size.